Muscular adaptations to training programs using the Nordic hamstring exercise or the stiff-leg deadlift in rugby players - Marchiori, C. L.; Medeiros, D. M.; Severo-Silveira, L.; Oliveira, G. d. S.; Medeiros, T. M.; Ribeiro-Alvares, J. B. d. A.; Baroni, B. M. (Sport Sciences for Health, 2022)
Background Muscular responses to training programs with the Nordic hamstring exercise (NHE) have been widely investigated to understand its preventive effects on muscle strain injury. Conversely, little is known about muscular responses to the stiff-leg deadlift (SLD), an exercise that preferably activate the biceps femoris long head, precisely the knee flexor muscle most commonly injured.